2007
DOI: 10.1051/agro:2007005
|View full text |Cite
|
Sign up to set email alerts
|

Implementing isolation perimeters around genetically modified maize fields

Abstract: -Due to the growing cultivation area of genetically modified (GM) maize and the rising number of GM maize varieties commercially available to European farmers, the co-existence between GM and non-GM maize is becoming a burning issue in some European regions. Hence, Member States are imposing or discussing specific co-existence measures to keep the adventitious presence of GM material in non-GM produces below the established labelling threshold. As maize is a cross-pollinated crop that uses wind for the dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…Van de Wiel et al (2009) in the field trials in the Netherlands concluded that the grain admixtures as a consequence of pollen mediated gene transfer from GM maize were much lower: 0.080-0.084% at 25 m and 0.005-0.007% at 250 m, respectively. Our results contributed to and confirmed several previous conclusions as published by Gustafson et al (2006), Messean et al (2006), Devos et al (2007), and Sandivo et al (2008) who observed that the maize pollen grains flow and pollen mediated gene transfer decline rapidly with increased distance. These studies do also draw the attention to the impact of the isolation distances for the implementation, as well as to the negative impact on the feasibility and production cost if disproportionate measures should be implemented.…”
Section: Methodssupporting
confidence: 93%
“…Van de Wiel et al (2009) in the field trials in the Netherlands concluded that the grain admixtures as a consequence of pollen mediated gene transfer from GM maize were much lower: 0.080-0.084% at 25 m and 0.005-0.007% at 250 m, respectively. Our results contributed to and confirmed several previous conclusions as published by Gustafson et al (2006), Messean et al (2006), Devos et al (2007), and Sandivo et al (2008) who observed that the maize pollen grains flow and pollen mediated gene transfer decline rapidly with increased distance. These studies do also draw the attention to the impact of the isolation distances for the implementation, as well as to the negative impact on the feasibility and production cost if disproportionate measures should be implemented.…”
Section: Methodssupporting
confidence: 93%
“…In scientific and regulatory communities, the debate about coexistence has been centered mainly on the following aspects: preventive coexistence measures needed to keep the adventitious presence of GM material in non-GM products below established tolerance thresholds [5,[7][8][9][10][15][16][17][18]; the feasibility and costs of implementing such measures [16,[19][20][21][22][23]; segregation costs and potential economic losses resulting from adventitiously co-mingled products [24][25][26]; who should bear the costs of coexistence measures [2,14]; and who should redress the incurred economic losses due to adventitious mixing [13]. Although these aspects are of fundamental importance when discussing coexistence strategies, they do not take into account the economic incentives for coexistence.…”
Section: Current Perspective On Coexistencementioning
confidence: 99%
“…In dieser Arbeit wird eine Methode dargestellt, und deren Ergebnisse mit anderen Arbeiten verglichen [1][2], mit der die räumliche Verteilung von Maisanbauflächen, auch von GV-Sorten, in einer Region simuliert werden kann. Die Ergebnisse können zunächst Aussagen darĂĽber liefern, in welchem Umfang das räumliche Nebeneinander von Nicht-GV-Mais und GV-Mais in einer Region möglich und in welchen Gebieten Koexistenz problematisch ist.…”
Section: Hintergrundunclassified